Determination of Heterotic Groups in Nepalese Yellow Maize Populations - Gurung, Dil Bahadur; George, Maria Luz C.; Delacruz, Quirino D. (Nepal Journal of Science and Technology, 2010)
Assigning germplasms into different heterotic groups is fundamental for exploitation of heterosis for hybrid development. An experiment was conducted in order to establish heterotic groups of some maize populations. Line x tester design was used for making crosses. Ten open pollinated varieties were used as lines and four as testers. Forty crosses along with their parents were evaluated in a randomized complete block design with three replications. Three testers were open pollinated varieties and one tester was a NML-2, an inbred line developed by CIMMYT. Basis of grouping the germplasms into different heterotic groups was specific combining ability (SCA) effects for grain yield. Population 46C1, Rampur So3Eo2, and Rampur So3Fo2 showed positive SCA effects with NML-2, and negative with Arun-4. These germplasms were assigned into heterotic group A. Similarly, Upahar, Across 9331, Population 35C5 and Narayani had positive SCA effects with Arun-4 and negative with NML-2 and grouped into heterotic group B. Likewise, Manakamana-2 and Hill Pool Yellow were placed into AB heterotic group, which displayed positive SCA effects with both testers. Khumal yellow had shown negative effects with both testers and put into undetermined group. This way, three heterotic groups were established based on the SCA effects. These heterotic groups are potential sources for inbred line development. Keywords: Lines; Testers; Heterotic effects; Specific combining ability effects; Heterotic groupings DOI: 10.3126/njst.v10i0.2802 Nepal Journal of Science and Technology Volume 10, 2009 December Page: 1-8